Estimation of outdoor and indoor effective dose and ex-cess lifetime cancer risk from Gamma dose rates in Gonabad, Iran - Reza Jafari; Hassan Zarghani (Brazilian Journal of Radiation Sciences, 2017)
Humans' background gamma irradiation in the indoor and outdoor environments is a major concern in the world. The study area was Gonabad city. Four stations and buildings for background radiation measurement of outdoor and indoor were randomly selected and the G.M detector (X5C plus) was used. All dose rates on display of survey meter were recorded and mean of all data in each station and buildings was computed and taken as measured dose rate of that particular station. The average dose rates of background radiation were 84.2 nSv/h for outdoor and 108.6 nSv/h for indoor, maximum and minimum dose rates were 88.9 nSv/h and 77.7 nSv/h for outdoor measurements and 125.4 nSv/h and 94.1 nSv/h for indoor measurements, respectively. Results show that the annual effective dose is 0.64 mSv, which compare to global level of the annual effective dose 0.48 mSv is high. Estimated excess lifetime cancer risk was 2.24×10-3, indicated that it is large as compared to the world average value of 0.25×10-3.